Ultra low-voltage low-power CMOS 4-2 and 5-2 compressors for fast arithmetic circuits - Chang, Chip Hong (2009)
This paper presents several architectures and designs of low-power 4-2 and 5-2 compressors capable of operating at ultra low supply voltages. These compressor architectures are anatomized into their constituent modules and different static logic styles based on the same deep submicrometer CMOS process model are used to realize them. Different configurations of each architecture, which include a number of novel 4-2 and 5-2 compressor designs, are prototyped and simulated to evaluate their performance in speed, power dissipation and power-delay product. The newly developed circuits are based on various configurations of the novel 5-2 compressor architecture with the new carry generator circuit, or existing architectures configured with the proposed circuit for the exclusive OR (XOR) and exclusive NOR (XNOR) [XOR–XNOR] module. The proposed new circuit for the XOR–XNOR module eliminates the weak logic on the internal nodes of pass transistors with a pair of feedback PMOS–NMOS transistors. Driving capability has been considered in the design as well as in the simulation setup so that these 4-2 and 5-2 compressor cells can operate reliably in any tree structured parallel multiplier at very low supply voltages. Two new simulation environments are created to ensure that the performances reflect the realistic circuit operation in the system to which these cells are integrated. Simulation results show that the 4-2 compressor with the proposed XOR–XNOR module and the new fast 5-2 compressor architecture are able to function at supply voltage as low as 0.6 V, and outperform many other architectures including the classical CMOS logic compressors and variants of compressors constructed with various combinations of recently reported superior low-power logic cells.